KUNCI KEBERHASILAN PEMBERDAYAAN MASYARAKAT DAN PELESTARIAN HUTAN DI TANGAN PENYULUH KEHUTANAN - Hardiatmi, Sri - (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2010)
ABSTRAC The threatening to forest conservation is now in the greatest level. This is caused by the increase in number of the people and also the increase of basic needs such as home, food, and cloth. To anticipate thet destruction, yhe government has done many efforts to support the raise of the economic exertion for the people who live nearby the forest. This effort cannot be separated wit the activity of the forest ranger. A forest ranger is responsible to do the supporting activity such as workshop. He has to take a real participation in the process of behavior changing among the people so that they are able and willing to do transformation to aim the productivity’s increasing, a good living earn, and a good prosperity. A forest ranger needs to have special characters.they are : 1. Humble2. Role model3. Protective like a parent4. Friendly5. Motivator6. Flexible in facing changes in live Key words : Forestry, Agro forestry, people around thr forest Ranger.